'For peace and defence of the Soviet Union': the leadership of British Communism in the Popular Front era, 1935–1939. (2nd January 2023) - McIlroy, John; Campbell, Alan
ABSTRACT: This prosopographical investigation of the Central Committee (CC) of the British Communist Party during the Popular Front era analyses the origins, occupations, political careers and destinations of the 47 Communists who served on the CC in these years. The transition from Third Period leftism to class collaboration found minimal reflection in the characteristics of the Communist leadership, which remained in line with those of the preceding cohort. The Popular Front group was slightly older, the percentage of women declined and attention to the middle class saw only marginal increase in the numbers that experienced higher education. There were more Scots, fewer English while turnover remained high. 'Debutantes' were younger and relatively raw compared with the 'Continuation Group' − 40% of newcomers had joined the CPGB during the Third Period. However, a 'core' whose CC service stretched back to the early 1920s and a 'core of the core' who endured into the 1950s ensured continuity. The integration of CC members into the party bureaucracy observed in earlier years was maintained: 75% of CC representatives occupied full-time posts. Previous articles provided life histories of the 'Continuation Group'; the biographical focus here is on the 'Debutantes'. But the majority of committee members were 'practical' working-class activists. Executors of policy, in the end they left theory and strategy to the Comintern and the Soviet elite.